Pastoral Counselling and Traditional Theology - Evans, Donald D. (Scottish journal of theology, 1958)
Is there a conflict between the principles of pastoral counselling and traditional Christian theology?In discussing this question, I shall consider Carroll A. Wise' Pastoral Counselling as a representative statement of counselling principles. What I mean by ‘traditional’ theology will, I hope, become reasonably clear in the course of the essay.